2015
DOI: 10.1136/bmj.h1991
|View full text |Cite
|
Sign up to set email alerts
|

Rise of waterpipe smoking

Abstract: When we started investigating the waterpipe more than a decade ago, 1 we knew that we were facing something that could have serious effects on global health. We did not know whether this was a passing fad or the full spectrum of risks the waterpipe poses to individuals and society.Considerable strides in understanding the public health impact of waterpipe smoking have been made since. At the same time, our worst predictions of an escalating global epidemic have been vindicated. 2 Data from the Global Tobacco S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Cigarette and nass users were further classified as former (those who quit more than 1 year before enrolment) or current users at baseline, and categorised by starting age and average lifetime intensity of use. Waterpipe use could not be classified in a similar way both because of the small number of users and the intermittent nature of its use 19. Cumulative waterpipe use (waterpipe-years) was calculated by multiplying duration of use by average number of times per day during each period of use, and was summed over the periods.…”
Section: Methodsmentioning
confidence: 99%
“…Cigarette and nass users were further classified as former (those who quit more than 1 year before enrolment) or current users at baseline, and categorised by starting age and average lifetime intensity of use. Waterpipe use could not be classified in a similar way both because of the small number of users and the intermittent nature of its use 19. Cumulative waterpipe use (waterpipe-years) was calculated by multiplying duration of use by average number of times per day during each period of use, and was summed over the periods.…”
Section: Methodsmentioning
confidence: 99%
“…This biennial Survey monitors the patterns of tobacco use among primary (US grade 4-6) and secondary school students (US grade 7-12) in Hong Kong (Lo et al 2013). The 2012/2013 data were collected from October 2012 to April 2013.…”
Section: Data Sourcementioning
confidence: 99%
“…School refusals were mainly due to administrative reasons (e.g., busy class schedule). We compared the student sample characteristics (sex, grade and age distribution) with 2012/2013 Hong Kong school student enrollment data, and found that our sample well represented the overall secondary school student population as indicated by small Cohen's effect size (range from 0.05 to 0.21) (Lo et al 2013).…”
Section: Data Sourcementioning
confidence: 99%
“…In 2015, 18 countries in western and central Europe had a smoking prevalence among girls, aged between 15 and 19 years, higher than 15%, and only three countries worldwide had significant decreases in adolescent smoking in the period from 2005 to 2015 1 . During the last decade, alternative smoke and smokeless products have become available and are being increasingly used; most popular are electronic cigarettes (e-cigarettes) and waterpipe, and also smokeless products such as snuff and chewing tobacco [2][3][4][5] . While there is little doubt that these products in themselves are less dangerous than cigarettes 6,7 , they are not harmless and there is concern that their use is associated with an increased risk of smoking initiation 3,[8][9][10] .…”
mentioning
confidence: 99%
“…During the last decade, alternative smoke and smokeless products have become available and are being increasingly used; most popular are electronic cigarettes (e-cigarettes) and waterpipe, and also smokeless products such as snuff and chewing tobacco [2][3][4][5] . While there is little doubt that these products in themselves are less dangerous than cigarettes 6,7 , they are not harmless and there is concern that their use is associated with an increased risk of smoking initiation 3,[8][9][10] . High school constitutes a time of transition characterized by physical, psychological and social changes during which environment and opinions of peers become increasingly important to young people while parents' influence declines [11][12][13] .…”
mentioning
confidence: 99%